A Sociological-Ideological Approach to Interpreting 1 Corinthians 7:1-11: The Perspective on Marriage in the Corinthian Church - Raulina, Raulina (Theological Journal Kerugma, 2024)
This article discusses the sociological-ideological interpretation of 1 Corinthians 7:1-11, where Paul responds to the Corinthians' questions regarding marriage and celibacy. In this analysis, the social and ideological context of Corinthian society serves as the basis for understanding Paul's views. By considering the moral conditions and social structure of Corinth, the article examines how the local worldview influenced the interpretation of the text, as well as how the biblical text impacts the social life of the church. The research findings indicate that Paul's decisions about marriage and celibacy were not based on absolute principles, but rather on the specific sociological circumstances in Corinth at the time. Paul's perspective on marriage is also closely related to the Christian teaching on the sacred relationship between Christ and His church. This article emphasizes the importance of considering the social context when interpreting biblical texts, particularly in understanding issues related to family and personal relationships within the church community.